2016
DOI: 10.1002/advs.201600189
|View full text |Cite
|
Sign up to set email alerts
|

Visible and Near‐Infrared Photothermal Catalyzed Hydrogenation of Gaseous CO2 over Nanostructured Pd@Nb2O5

Abstract: The reverse water gas shift (RWGS) reaction driven by Nb2O5 nanorod‐supported Pd nanocrystals without external heating using visible and near infrared (NIR) light is demonstrated. By measuring the dependence of the RWGS reaction rates on the intensity and spectral power distribution of filtered light incident onto the nanostructured Pd@Nb2O5 catalyst, it is determined that the RWGS reaction is activated photothermally. That is the RWGS reaction is initiated by heat generated from thermalization of charge carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(44 citation statements)
references
References 73 publications
(110 reference statements)
0
41
0
Order By: Relevance
“…In addition, plasmon decay can lead to enhanced photothermal conversion, which has been employed to promote chemical reactions because reaction rates are generally dependent exponentially on temperature . Nb 2 O 5 catalysts loaded with Pd nanoparticles have recently been reported to be able to initiate the hydrogenation of gaseous CO 2 by heat generated from the plasmon resonance of the Pd nanoparticles under visible and NIR light . The investigation of using the plasmonic photothermal effect to enhance chemical reactions is still at its early stage.…”
Section: Localized Surface Plasmon Resonancementioning
confidence: 99%
“…In addition, plasmon decay can lead to enhanced photothermal conversion, which has been employed to promote chemical reactions because reaction rates are generally dependent exponentially on temperature . Nb 2 O 5 catalysts loaded with Pd nanoparticles have recently been reported to be able to initiate the hydrogenation of gaseous CO 2 by heat generated from the plasmon resonance of the Pd nanoparticles under visible and NIR light . The investigation of using the plasmonic photothermal effect to enhance chemical reactions is still at its early stage.…”
Section: Localized Surface Plasmon Resonancementioning
confidence: 99%
“…[17][18][19][20] Ap ossible approachf or efficient conversion of solar energy is based on the photothermal effect of nanoparticles (NPs) to generate hot carrierst op articipate in redox reactions, or to dissipate the absorbed photon energy into heat to accelerate the reactionrate. [21][22][23][24][25] Titanium dioxide (TiO 2 )i st he most representative material for photocatalysis, which has the advantages of low cost, nontoxic, high photoelectric conversione fficiency,h igh photocata-lytic activity,h igh chemicals tability,l arge specific surface area and pore volume. [26][27][28][29] The anatase TiO 2 with ag ood photocatalytic property usually has ab and gap of about 3.2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Following this work, many other studies have been reported. Ozin et al [119] used Nb 2 O 5 nanorod-supported Pd nanocrystals with visible and NIR light to realize CO 2 reduction into CO. The CO 2 hydrogenation rate with this hybrid catalyst under visible and NIR light can reach 1.8 mmol h −1 g −1…”
Section: Photothermal Catalysismentioning
confidence: 99%